The use of tools to support oral lesion description in oral medicine referrals - Caroline Zimmermann; Maria Inês Meurer; Josimari Telino de Lacerda; Ana Lúcia Schaefer Ferreira de Mello; Liliane Janete Grando (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract: Poor description of oral lesions jeopardize the prioritization of appointments in Oral Medicine. The present study investigated whether the use of support tools changes the quality of descriptions focusing on health care prioritization. Two oral lesions (A and B) were described by 64 dental students and 48 dentists using three methods: (a) without support tools (free); (b) using the oral examination form from the Specialties Manual in Oral Health/Brazilian Ministry of Health (SMOH form); and (c) using the OralDESC guideline. The descriptions were compared with a gold standard and percentage of agreement was analyzed by the Kruskal-Wallis and Dunn's tests (p<0.05). Descriptions with the OralDESC presented higher information quality. Considering items essential for prioritization, the OralDESC demonstrated better performance for lesion A; for lesion B, free descriptions and descriptions using the OralDESC were of higher quality than those using SMOH form. Therefore, the OralDESC offered greater support for the description of oral lesions for health care prioritization in Oral Medicine.